Medan Nikah Clinic's Da'wah Strategy Against the Marriage Is Scary Trend: A Phenomenological Study among Young Muslims - Azizah, Siti; Muin, Mohd Iqbal Abdul (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The “Marriage Is Scary” trend reflects doubts, fears or concerns about married life that are often publicized through personal or reflective content on social media. The concerns often expressed stem from infidelity, domestic violence, marital unpreparedness, gender inequality, and poor conflict management leading to divorce. This study aims to analyze the da'wah strategy implemented by Medan's Nikah Clinic in dealing with the marriage is scary trend. The research uses a qualitative method with a phenomenological approach. Data were collected through observation, in-depth interviews with six program alumni, and documentation of activities at Nikah Clinic Medan, located in Medan City, North Sumatra. The data analysis technique was conducted by Miles and Huberman which includes data reduction, data presentation, and conclusion drawing. The results showed that Medan Nikah Clinic implemented a holistic education-based da'wah strategy, including: (1) organizing pre-marital lectures based on the integration of religious values and psychology; (2) involving professional da'i with interpersonal communication competencies; (3) establishing discussion forums and confidence-based matchmaking consultations; (4) outbound programs for character strengthening and partner cooperation; and (5) optimizing digital media for adaptive da'wah. This strategy is effective in building the mental, emotional, and spiritual readiness of prospective couples, which is reflected in the participants' narratives of increased self-confidence and decreased anxiety about marriage. This research contributes to enriching the study of da'wah strategies based on contemporary social phenomena and provides practical implications for the development of pre-marital education programs for the younger generation.